(untitled) (Significação: Journal of Audiovisual Culture, 2007)
This work proposes a brief analysis on the use of the chess garoe analogy in the language sciences (F. de Saussure, L. Hjelroslev, L.Wittengstein). After some considerations on the nature of chess garoe and its understanding as a situation of interaction between two subjects, this paper presents, by the seroantic approach o f the lexeme "garoe", the analysis ofthe narrative process ofthe subject "player" and its strategies.